Soaking in Seawater of Rice Straw Increases In vitro Dry Matter and Organic Matter Digestibility - H. Husnaeni; M. Arifin Amril; Sjamsuddin Rasjid (Chalaza Journal of Animal Husbandry, 2017)
This research aims to improve the digestibility and nutritional value of rice straw as a ruminant animal feed and determine the effect of long soaking in sea water of rice straw on digestibility in vitro dry matter and organic matter. The used materials in this study are a bales machine, weighing scales, rapiah rope, poly bags, rice straw varieties Ciliwung obtained from rice fields in Bantimurung, sea water with 2.71% saline, as well as tools and chemicals for analysis of in vitro dry matter and organic matter digestibility with pepsin, calculus method. This study is done based on Randomized Complete  Design (RCD) with 5 treatments and 4 replications. Variance based on the long soaking treatment gives the nature of the response curve linear on the digestibility of dry matter and also to organic matter digestibility. The magnitude of the correlation length relationship soaking rice straw and with sea water for in vitro dry matter and organic matter digestibility that is 96.5% and 96.8% respectively. Based on the results of research and discussion can be concluded that rice straw is soaked with sea water 3-12 days producing dry matter digestibility and organic matter are higher than the rice straw that is not soaked with sea water. Soaking of the sea water for 3-12 days increase the digestibility of dry matter and organic matter.